2021
DOI: 10.1016/j.jcou.2021.101556
|View full text |Cite
|
Sign up to set email alerts
|

CH4 reforming with CO2 in a nanosecond pulsed discharge. The importance of the pulse sequence

Abstract: The plasma dry reforming reaction of methane with carbon dioxide is investigated in a nanosecond repetitively pulsed discharge, a type of plasma that offers some of the highest performance and non-equilibrium characteristics. The experiment's purpose was to examine the effect of varying the sequence of high-voltage pulses. We find that when successive pulses are closer than 500 μs, a memory-dominated regime gradually develops, which influences subsequent breakdown events. While reactant conversions increase wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Previous findings refer to a situation where the HV pulse regularly repeats with an interval long enough so that each pulse is independent of the previous one and, therefore, equivalent to it. Instead, the situation changes substantially when the interpulse time is short enough that a memory effect develops because successive discharges occur in a gas mixture perturbed by the preceding ones. ,, We produced such a condition by using packets of five pulses, called bursts, where the temporal separation of the plasma pulses ( t p ; the interpulse time) could be varied; we chose t p = 100 and 33 μs (see Figure ). Typical values of conversion determined via gas chromatography at the exit of the reactor in similar operating conditions and with a specific energy input of 1.4 eV molecule –1 are 15 ± 1% for regularly repeated pulses and between 19 and 22% for burst with t p < 100 μs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings refer to a situation where the HV pulse regularly repeats with an interval long enough so that each pulse is independent of the previous one and, therefore, equivalent to it. Instead, the situation changes substantially when the interpulse time is short enough that a memory effect develops because successive discharges occur in a gas mixture perturbed by the preceding ones. ,, We produced such a condition by using packets of five pulses, called bursts, where the temporal separation of the plasma pulses ( t p ; the interpulse time) could be varied; we chose t p = 100 and 33 μs (see Figure ). Typical values of conversion determined via gas chromatography at the exit of the reactor in similar operating conditions and with a specific energy input of 1.4 eV molecule –1 are 15 ± 1% for regularly repeated pulses and between 19 and 22% for burst with t p < 100 μs .…”
Section: Resultsmentioning
confidence: 99%
“…The daunting task of reducing the emission of greenhouse gases in the atmosphere and finding alternative energy sources to fossil fuels burdens our societies. The late Nobel prize laureate G. Olah proposed to produce synthetic fuels using CO 2 and green electricity to close the anthropogenic carbon cycle; at the same time, renewable energy is stored in value-added compounds. , For this purpose, plasma-catalysis-based technology is among the different implementations under development. In particular, atmospheric nanosecond repetitively pulsed (NRP) discharges have shown high efficiencies in converting CO 2 , providing strong motivation for fundamental investigations. , The core idea behind the plasma approach is exploiting the nonequilibrium features of gaseous discharges, which ideally allow directing the energy into CO 2 dissociation with minimum gas heating.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosecond Repetitively Pulsed (NRP) discharges have shown good performances in the reduction of CO 2 , both in dry reforming [1,2] and in pure CO 2 [3][4][5]. The fast transient nature of NRP discharges calls for time-resolved diagnostics for understanding mechanisms and the time evolution of the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to deepen the time-resolved characterisation of the pulsed discharge regimes by analysing the emission spectra of the NRP discharge used in [5]. Time-resolved emission spectroscopy studies of NRP discharges in CO 2 are not yet available in the literature. Studies in nitrogen and air mixture have been reported, mainly devoted to a characterisation of the spark regime and the streamer-to-spark transition [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are mostly based on physical or physicochemical phenomena [10][11][12] such as adsorption [13], absorption [14], membrane separation [15], or cryogenic techniques [16]. Among them, there exist also other ones, for example, chemical catalytic transformation [17][18][19], microbial electrochemical technologies [20], or hydratebased processes [21].…”
Section: Introductionmentioning
confidence: 99%